THE GENERAL DIRECTION OF THE PUBLIC HEALTH PROMOTION PROGRAM (Scientific journal of the Fergana State University, 2024)
In this scientific research work, the scientific essence of the changes in the population's organism is revealed on the basis of its repetition during the training of the public health program and its general directions and the introduction of this program into life activities, and the information obtained is physical training. It is explained by the fact that it helps to enrich and expand theoretical knowledge in the field of theory and methodology.